International Community Development Program - Sa’diah, Kamilah; Pawar, Avinash; Nasution , Siti Wardah Pratidina; Ekawati, Yuni Andri; Rahimah, Evida (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The International Community Development Program for community service is an initiative that involves collaboration between universities or institutions and international communities in efforts to improve societal well-being. Through international service activities, educational institutions can expand their network of cooperation with institutions from other countries. This opens opportunities for the exchange of knowledge, experiences, and cross-cultural resources. The program focuses on community empowerment through various activities such as outreach in senior citizen care centers aimed at providing education and special attention to the elderly who need care in terms of well-being. Additionally, a sharing session for the younger generation is conducted to enhance their capacity in facing future challenges. Another activity is a workshop on promoting batik weaving products to the youth, aimed at preserving local culture while encouraging innovation in the creative economy sector. The final activity, tree planting for environmental sustainability, serves as one of the climate change mitigation efforts and helps preserve biodiversity. The outcomes of this international community service program not only have a direct impact but also open opportunities for sustainable development across various sectors including social, cultural, and environmental areas in Palembang City.